Effect of classic back massage on spinal pain in a woman with large breasts - case report - Natalia Zielińska; Natalia Sokołowska; Remigiusz Sokolowski; Paula Dudek; Dominika Gębka; Grzegorz Srokowski; Wojciech Stemplowski; Walery Zukow (Kazimierz Wielki University, 2017)
Introduction. The most common ailment of the motion system is spinal pain. For one of the main reasons, it consider a sedentary lifestyle that weakens the musculo-skeletal system, obesity that increases spine load, sleep disorders resulting from unsettled positions during rest or sleep, and chronic stress. The use of massage can reduce the painful pain of the spine, by loosening the excessively tight spine muscles, the articular joints of the joints and the relaxation of the body. Objective. An assessment of the effect of classical spine massage on spinal pain in a woman with large breasts. Material and methods. 10 massage treatments of the classical ridge using olive oil were performed. Sessions took place 2-3 times a week after 30-50 minutes. Before and after intervention were measured: linear measurements of upper and lower limbs; Measurement of the first and short long and short for the upper and lower limbs for the upper and lower extremities; Measurement of the range of mobility of individual segments of the spine; Measurement of muscle strength of the cervical, thoracic and lumbar musculature of the upper limbs; Assessment of deviation from the symmetry of body posture. Also tested was the Cross Stroke Challenge, finger-to-floor test, lumbar vertebrae overtaxis test, Laseque test, Scherer test and Gilett test. Results. The difference in the range of motion, ie the flexion of the thorax and lumbar spine and the finger-to-floor examination, was statistically significantly different. After intervention the silhouette of the body was positioned closer to the vertical axis. The Laseque test for both lower limbs turned out to be negative. The difference in linear and limb length measurements and the Schober test was not statistically significant. The test of cross-provocation, the overtaking test for the lumbar spine movement and the Gillet test did not show deviations before or after intervention. Conclusions. Therapeutic massage of the classic back reduced the pain of the spine. Improved body posture and increased range of motion in individual spinal segments. In addition, no effect of classical massage on muscle strength and limb circumference was found.